Safety and Outcomes of Mechanical Thrombectomy in Acute Ischemic Stroke Attributable to Cardiological Diseases: A Scoping Review - Lucio D’Anna; Samir Abu‐Rumeileh; Giovanni Merlino; Raffaele Ornello; Matteo Foschi; Francesco Diana; Lorenzo Barba; Vincenzo Mastrangelo; Michele Romoli; Kyriakos Lobotesis; Francesco Bax; Fedra Kuris; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
There is limited evidence on the outcomes and safety of mechanical thrombectomy (MT) among patients with acute ischemic stroke (AIS) in the context of cardiac diseases. Our study reviews MT in AIS within the context of cardiac diseases, aiming to identify existing and emerging needs and gaps. PubMed and Scopus were searched until December 31, 2023, using a combination of cardiological diseases and “mechanical thrombectomy” or “endovascular treatment” as keywords. Study design included case reports/series, observational studies, randomized clinical trials, and meta‐analyses/systematic reviews. We identified 943 articles, of which 130 were included in the review. Results were categorized according to the cardiac conditions. MT shows significant benefits in patients with atrial fibrillation (n=139) but lacks data for stroke occurring after percutaneous coronary intervention (n=2) or transcatheter aortic valve implantation (n=5). MT is beneficial in AIS attributable to infective endocarditis (n=34), although functional benefit may be limited. Controversy surrounds the functional outcomes and mortality of patients with AIS with heart failure undergoing MT (n=11). Despite technical challenges, MT appears feasible in aortic dissection cases (n=4), and in patients with left ventricular assist device or total artificial heart (n=10). Data on AIS attributable to congenital heart disease (n=4) primarily focus on pediatric cases requiring technical modifications. Treatment outcomes of MT in patients with cardiac tumors (n=8) vary because of clot consistency differences. After cardiac surgery stroke, MT may improve outcomes with early intervention (n=13). Available data outline the feasibility of MT in patients with AIS attributable to large‐vessel occlusion in the context of cardiac diseases.